2020
DOI: 10.1002/adbi.201900248
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule from Natural Phytochemical Mimics Dietary Restriction by Modulating FoxO3a and Metabolic Reprogramming

Abstract: Many studies utilizing animal models have revealed the genetic and pharmacogenetic modulators of the rate of organismal aging. However, finding routes for healthy aging during extended life remains one of the largest questions. With regards to an antiaging reagent, it has been shown that natural phytochemical syringaresinol (SYR) delays cellular senescence by activating sirtuin1 (SIRT1). Here, it is found that SYR treatment results in metabolic changes similar to those observed during dietary restriction (DR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Collectively, the DR-related metabolite threonine increased the healthspan by the induction of antioxidative protection. It was furthermore interesting to note that previous studies on anti-aging compounds and metabolites, which reported DR-mimic activity, including syringaresinol 27 , metformin 28 , and α-ketoglutarate 29 , also increased the threonine content in C. elegans (Fig. 1j ).…”
Section: Resultsmentioning
confidence: 75%
“…Collectively, the DR-related metabolite threonine increased the healthspan by the induction of antioxidative protection. It was furthermore interesting to note that previous studies on anti-aging compounds and metabolites, which reported DR-mimic activity, including syringaresinol 27 , metformin 28 , and α-ketoglutarate 29 , also increased the threonine content in C. elegans (Fig. 1j ).…”
Section: Resultsmentioning
confidence: 75%
“…Collectively, the DR-related metabolite threonine increased the healthspan by the induction of antioxidative protection. It was furthermore interesting to note that previous studies on anti-aging compounds and metabolites, which reported DR-mimic activity, including syringaresinol 26 , metformin 27 , and α-ketoglutarate 28 , also increased the threonine content in C. elegans (Fig. 1j).…”
Section: Identification Of Longevity-related Metabolites and Their Effects On C Elegans Healthspanmentioning
confidence: 75%
“…For example, in vitro results showed that syringaresinol exerted antioxidant activities, hence could affect the pathogenesis of fatigue (84). Besides, syringaresinol can activate SIRT1, which increases the antioxidant capacity through activation of nuclear factor (erythroid-derived 2)-like 2 (85). In general, compounds with similar chemical structures tend to have similar biological properties.…”
Section: Discussionmentioning
confidence: 99%